(untitled) (Journal of Additive Manufacturing Technologies, 2022)
Laser Powder Bed Fusion (L-PBF) is one of the promising Additive Manufacturing (AM) technologies to build relatively smooth surfaces belong to complex geometries with its overall technology readiness level. However, this may depend on the other parameters such as built orientation, support structures etc. Despite many advantages of AM, surface roughness of L-PBF’ed parts may still not be met in as-built condition the tight requirements of aviation industry. In this study, the surface roughness assessment of L-PBF’ed as-built Alloy 718 parts using virgin powder is evaluated by utilizing several post processes beyond the industrial preferences, in aviation standards. The surface roughness is consequently optimized based on orientation in order to define robust manufacturing tolerances in AM of aviation parts. Closed clearances or smooth surface profiles are perfectly needed in those parts to improve several aspects such as fatigue life span. In the scope of this study, Grit Blasting, Glass Bead Peening, Chemical Milling, Ultrapolish and some of their combinations on five different sloping angles were studied, surface quality were evaluated with profilometer in addition to weight loss effects based on the stock loss method. The outcomes of the study will be used as reference in the future works of TEI.